2018
DOI: 10.1155/2018/7358205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on 3D Roughness and Shear Failure Mechanism of Rock Mass Discontinuity

Abstract: A set of systematic experimental methods, including 3D accuracy scanning and identification of discontinuous surface topography, physical model construction, and laboratory direct shear experiment under different directions and normal stresses, was proposed to research the influence of discontinuity roughness on strength and deformation of discontinuity. During physical model construction of discontinuity, three types of discontinuity and rough natural rock joint surface models were constructed and moulded. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Due to the interest in obtaining mechanical strength data from sample geometry, there are several contributions that attempt to extrapolate one data from another [14,15]. There is a large consensus that the contact between joint lips during the shearing process occurs in those asperities that oppose the shearing direction, with the highest percentage of damage concentrated in those with the greatest inclination [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the interest in obtaining mechanical strength data from sample geometry, there are several contributions that attempt to extrapolate one data from another [14,15]. There is a large consensus that the contact between joint lips during the shearing process occurs in those asperities that oppose the shearing direction, with the highest percentage of damage concentrated in those with the greatest inclination [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, they established the relationship between three-dimensional morphology parameters and the friction coefficient. e study of the relationship between the joint surface morphology parameters and dilatancy angle has drawn increasing attention [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Zhao revealed that the attenuation factor in a filled fracture increases with higher water content from an air-dry state to a saturated state [20]. Wei et al proposed a set of systematic experimental methods to research the influence of discontinuity roughness on strength and deformation of discontinuity [21].…”
Section: Introductionmentioning
confidence: 99%